Prediction of Salmonella inactivation in sliced tomato subject to high pressure processing and trans-cinnamaldehyde treatment using selective and non-selective growth media for survival evaluations - Zhou, Siyuan; Sheen, Shiowshuh; Zhao, Guohua; Chuang, Shihyu; Liu, LinShu (Food control, 2020)
High pressure processing (HPP) is an effective non-thermal food operation means to reduce foodborne illness risks. Trans-cinnamaldehyde (TC) is a GRAS compound widely used in food applications for flavoring and recently found the potential to enhance microbial inactivation with HPP. For the first time, this study investigated combination effects of relatively low hydrostatic pressure level (i.e. 150, 200 and 250 MPa), operation time (i.e. 4, 8 and 12 min) and TC concentration (i.e. 200, 400 and 600 ppm) on Salmonella inactivation in sliced tomato by using both selective (i.e. XLT4 agar plates) and non-selective (i.e. Aerobic Petrifilms™) growth media for microbial survival evaluations. Linear and dimensionless non-linear regression models were developed, evaluated and validated for providing comparative information for descriptions and predictions of the inactivation effects. The results showed that a strong synergistic inactivation effect between hydrostatic pressure and TC was observed, which could explain for the great inactivation effects of the combination treatments (maximum reduction > 6 log CFU/g). The inactivation of Salmonella in XLT4 agar plate counts was significantly larger (up to 1.96 log CFU/g) than in Aerobic Petrifilm™ counts (p < 0.05), suggesting using non-selective growth media could be a more conservative choice than selective growth media, ensuring a higher microbial safety level. According to the novel 4-dimensional response surface plots of developed models, hydrostatic pressure level played the most important role in the inactivation. This study provides valuable reference information to the current HPP manufacturers dealing with tomato products. •Studied Salmonella inactivation in sliced tomato by HPP and TC.•Utilized a relatively low hydrostatic pressure range (150–250 MPa).•Observed strong synergistic effect between hydrostatic pressure and TC.•Inactivation on selective media was larger than non-selective media.•Established linear and dimensionless non-linear prediction models.